Analysis of Indonesian Students Scientific Literacy Ability in Chemistry Learning: A Systematic Literature Review - Adek Diah Murti; Hernani Hernani; Soja Siti Fatimah (Global READ Center, 2024)
This study aims to examine the results of the analysis of scientific literacy abilities of Indonesian students in chemistry learning. The method used is Systematic Literature Review (SLR), which consists of five stages, namely question formulation, locating studies, study selection and evaluation, analysis and synthesis, reporting and using the results. Based on a study of 15 reputable journals indexed scopus (International Journal) and sinta (National Journal), the scientific literacy abilities of Indonesian students at the high school level and the education of prospective teachers are in the sufficient category, but there are still many who are in the low category. This is because students are not familiar with scientific literacy questions and learning which rarely trains individuals to make arguments based on observations or investigations, making it difficult for them to work on questions that require an analysis of existing scientific evidence or facts. Therefore, it is necessary to make efforts to improve scientific literacy skills through the application of learning models that train the ability to apply scientific knowledge that has been obtained in solving problems in everyday life. Problem-based learning models, ethnoscience-based learning, contextual-based guided inquiry learning, and also project-based learning.